Performing metaphoric creativity across modes and contexts - Hidalgo-Downing, Laura; Kraljevic Mujic, Blanca (Figurative thought and language ;, 2020)
"The creative potentiality of metaphor is one of the central themes in research on creativity. The present volume offers a space for the interdisciplinary discussion of the relationship between metaphor and creativity by focusing on (re)contextualization across modes and socio-cultural contexts and on the performative dimension of creative discourse practices. The volume brings together insights from Conceptual Metaphor Theory, (Critical) Discourse approaches to metaphor and Multimodal discourse analysis. Creativity as a process is explored in how it emerges in the flow of experience when talking about or reacting to creative acts such as dance, painting or music, and in subjects' responses to advertisements in experimental studies. Creativity as product is explored by analyzing the choice, occurrence and patterning of creative metaphors in various types of (multimodal and multisensorial) discourses such as political cartoons, satire, films, children's storybooks, music and songs, videos, scientific discourse, architectural reviews and the performance of classical Indian rasa"--